Illumination and Calligraphy in Malay Letters - Abdul Razak Abdul Karim; Reniwati Reniwati (Masyarakat Linguistik Indonesia Universitas Andalas, 2017)
Malay manuscripts contain all kinds of knowledge. The manuscripts not only tell stories, they also depict various knowledge within the minds of past generations. In this paper discuss elements of illumination and the use of calligraphy in Malay letters on past Malay letters. The research is limited on Malay letters in social letters in the period 1521-1899. Malay society in the olden days practiced very fine arts as shown in the Malay letters through illumination and through the use of various types and designs of calligraphy. They used the world of nature to express their feelings. This paper will reveal that the traditional Malay society was not impoverished of art, that they had the highest aesthetic value in art, even beyond comparison with the present.